WPI Hydrogels with a Prolonged Drug-Release Profile for Antimicrobial Therapy - Valentina O. Plastun; Ekaterina S. Prikhozhdenko; Olga I. Gusliakova; Svetlana V. Raikova; Timothy E. L. Douglas; Olga A. Sindeeva; Oksana A. Mayorova (Pharmaceutics, 2022)
Infectious sequelae caused by surgery are a significant problem in modern medicine due to their reduction of therapeutic effectiveness and the patients’ quality of life.Recently, new methods of local antimicrobial prophylaxis of postoperative sequelae have been actively developed. They allow high local concentrations of drugs to be achieved, increasing the antibiotic therapy’s effectiveness while reducing its side effects. We have developed and characterized antimicrobial hydrogels based on an inexpensive and biocompatible natural substance from the dairy industry—whey protein isolate—as matrices for drug delivery. The release of cefazolin from the pores of hydrogel structures directly depends on the amount of the loaded drug and occurs in a prolonged manner for three days. Simultaneously with the antibiotic release, hydrogel swelling and partial degradation occurs. The WPI hydrogels absorb solvent, doubling in size in three days and retaining cefazolin throughout the duration of the experiment. The antimicrobial activity of cefazolin-loaded WPI hydrogels against Staphylococcus aureus growth is prolonged in comparison to that of the free cefazolin. The overall cytotoxic effect of cefazolin-containing WPI hydrogels is lower than that of free antibiotics. Thus, our work shows that antimicrobial WPI hydrogels are suitable candidates for local antibiotic therapy of infectious surgical sequelae.